PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, KUALITAS LAYANAN DAN STORE ATMOSPHERE TERHADAP KEPUASAN (Studi Pada Pelanggan Antariksa Coffeeshop Semarang) - Priyo Utomo; Ali Maskur (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study aims to analyze the effect of product quality, price perception, service quality, and store atmosphere on satisfaction (study on customers of Antariksa Coffeeshop Semarang). The population in this study is customer of Antariksa Coffeeshop Semarang who buys the product at least three times. The sample taken by the researcher in this study was 100 respondents with a sampling technique using purposive sampling, namely the technique of determining the sample using certain criteria. The data used in this study is primary data, using a questionnaire as a research instrument. The analytical tools used in this research are validity test with loading factor, reliability test with cronbach alpha, f test, coefficient of determination (R2), multiple linear regression, and hypothesis testing (t test). The result of this study indicate that product quality has a positive and significant effect on customer satisfaction, price perception has no significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, and store atmosphere has a positive and significant effect on customer satisfaction.